A Non-equilibrium Approach to Model Dynamic Composite Systems with Interface Transport*. Issue 24 (2016) - Romo-Hernandez, Aarón; Dochain, Denis; Ydstie, B. Erik; Hudon, Nicolas
Abstract: In this note, we derive a dynamical model that tracks the evolution of the internal energy, the volume and the molar compositions of composite systems. The proposed modeling approach considers interface transport using a non-equilibrium thermodynamic perspective and predicts dynamical trajectories to thermodynamic equilibrium. Both closed and open systems are considered and, for both cases, it is shown that expected equilibrium properties are recovered. Numerical simulations based on the proposed model show the potential of the proposed non-equilibrium approach for open and closed multiphase systems.